Endoscopy-assisted high anterior cervical approach in craniovertebral junction (CVJ) - Li, Pengfei; Wang, Kaixuan; Ji, Hongming; Zhang, Gangli; Chen, Shengli; Zhang, Shiyuan; Dunn, Ian F.; Hu, Changchen (Frontiers in Surgery, 2022)
Background: Surgery on the craniovertebral junction (CVJ) presents particular challenges owing to the close proximity of critical neurovascular structures and the brainstem. It is difficult for classic approaches to obtain the extra exposure of neurovascular structures of the CVJ in practice.The surgical approach to the craniovertebral junction (CVJ) offers specific challenges. We explored the feasibility of an endoscope-assisted high anterior cervical approach to the CVJ. Methods: We quantitatively assessed the surgical corridor to, and extent of exposure of, the CVJ in six cadaveric specimens, using 0° and 30° endoscopes. Results: The endoscope provided sufficient exposure of neurovascular structures and the brainstem in the CVJ. Resection of the anterior arch of C1 was avoided in minimal anterior clivectomy. After removing the odontoid, greater exposure of the CVJ was obtained. Conclusion: An endoscope-assisted high anterior cervical approach to the CVJ preserves cervical spine stability while minimizing the risk of neurovascular injury within the surgical corridor.